MOLECULAR MODELING STUDY OF BORIC ACID IMPRINTED POLYMER FOR QUARTZ CRYSTAL MICROBALANCE APPLICATION - Iqmal Tahir; Mohd Noor Ahmad; A.K.M. Shafiqul Islam; Dahyar Arbain (Jurnal Kimia (Journal of Chemistry), 2012)
Design of boric acid imprinted polymer has Been conducted using molecular modeling approach to fabricate thYn film for sensor applications on quartz crystal microbalance. The study was carried out to find an optimum mole ratio between boric acid as the template and methacrylic acid as functional monomer. Molecular modeling was performed using AM1 semiempirical – quantum mechanics on Hyperchem 8.0 software. The result showed was stabilite of supramolecular structure between boric acid and methacrylic acid on ratios of 1:3 and 1:6. Recommendation of boric acid imprinted polymer is suggested to synthesize on mole ratio of 1:3.